Dominasi Kepercayaan Pengguna: Analisis Kualitas Pelayanan dan Persepsi Harga Jasa Penyeberangan Rute Paciran-Bawean - Saskia Maharani; Andar Sri Sumantri; Sulistyowati Sulistyowati (Indonesian Maritime Researchers and Lecturers, 2025)
This study aims to analyze the influence of Service Quality, Price Perception, and Trust on the User's Interest in the ferry service of KMP Gili Iyang on the Paciran-Bawean route operated by PT. ASDP Indonesia Ferry (Persero) Cabang Paciran. This route plays a critical role as an essential logistics and social link for Bawean Island. The quantitative research used a survey method with an Incidental Sampling technique, involving 100 respondents who are users of the service. The collected data were analyzed using Multiple Linear Regression with SPSS V25. The partial hypothesis test results (t-test) show that Service Quality (β=0.80; p=0.033), Price Perception (β=0.69; p=0.038), and Trust (β=0.587; p=0.000) individually have a positive and significant impact on the User's Interest. The Trust variable was found to be the most dominant predictor, emphasizing the importance of integrity, competence, and operational consistency in essential and high-risk maritime transportation services. The adjusted R-squared value of 60.% indicates that this model provides a strong explanation for the variation in User's Interest. This study provides important implications for managing ferry services by improving service quality, competitive pricing, and building customer trust to increase user interest.